THE USE OF ANIMATED VIDEOS FOR THE DEVELOPMENT OF MULTICULTURAL-BASED CHARACTER VALUES IN FRENCH LANGUAGE LEARNING - Rohali, Rohali; Kusnawati, Tri; Rahmawati, Desi (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The integration of character education into learning is essential. This study developed an animated video focusing on multicultural character values in French language education for high school students. It also described the character values that emerged in schools teaching French through these multicultural animated videos. Utilizing the action research and development (R&D) model proposed by Dick et al. (2005), the results indicated that three animated videos could effectively incorporate 11 character values for both classroom and out-of-class learning. These character values include religious faith, independence, tolerance, cooperation, discipline, curiosity, love of peace, hard work, nationalism, multiculturalism, and responsibility. These values are evident and fostered throughout the learning process.